Activity of nine antimicrobial agents against Lancefield group C and group G streptococci. - Rolston, K V (1982)
The activity of nine antimicrobial agents against 44 strains of group C and group G streptococci was studied using a microtiter broth dilution technique. Several antimicrobial agents, including third-generation cephalosporins, the newer semisynthetic penicillins, and erythromycin, exhibited good activity against the organisms. Occasional tolerance to various agents was observed. No cross-tolerance was observed in this study.